Features of understanding public relations in Ukraine and European countries - Yevhen Leheza; Serhii Herasymchuk; Olena Banchuk-Petrosova; Vyacheslav Tylchyk; Volodymyr Rohalskyi (Ius Humani. Jornal do direito, 2023)
The purpose of the research is defining the concept of social relations from the point of view of theoretical, administrative, civil-legal aspects of legal regulation, considering scientists. Main content. The content of the concepts of “public relations” and “social relations” as political and legal entities with different paradigmatic definitiveness is substantiated. Methodology: The methodological basis of the research consists of comparative-legal and system analysis, formal-legal method, interpretation method, hermeneutic and methods of analysis and synthesis. Conclusions. It has been established that the term “public relations” characterizes relations between people, which provide for the unconditional priority of the economy over other spheres of society (political, ideological, cultural), where there is no place for a person with his values, rights and freedoms. At least, the latter do not acquire proper regulatory support.